Reading to Learn (R2L) Model to Activate Students on Reconstruction Short Story - Rahmad Husein; Restu Restu; Mariani Sembiring; Swesty Wulandari; Suri Andary; M.Arief Rahman (BIRCU, 2022)
Reading to learn (R2L) is developed by D. Rose and J.R. Martin for a teacher to guide students to read and to write a text. R2L model has four stages: preparing for reading, detailed reading, note-making, and joint construction. This article describes the implementation of the R2L model for students to reconstruct a short story in Bahasa Indonesia subject. A teacher and third-year students of Junior High School are involved in the study. The processes of teaching and learning for four meetings are recorded by a video camera. The data are presented for each meeting. The result depicts that by R2L with the inclusion of skimming, scanning, reading preparation, read in detail the students are able to identify the keywords, paraphrase, and reconstruct a new short story.